2016
DOI: 10.1016/j.jcin.2016.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Coronary Interventions for the Treatment of Stenoses in Small Coronary Arteries

Abstract: Early generation SES yielded the most favorable angiographic and clinical outcomes for the treatment of stenoses in small coronary arteries. New generation DES need to be evaluated against this standard in future randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
58
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 52 publications
1
58
1
1
Order By: Relevance
“…Recently, the BELLO (Balloon Elution and Late Loss Optimization) randomized trial demonstrated that the treatment of small‐vessel disease with a paclitaxel DCB was associated with less angiographic late loss and similar rates of restenosis and revascularization when compared to “first‐generation” paclitaxel‐eluting stents (PES) at 6‐months and a lower incidence of major adverse cardiac event (MACE) at 3‐year follow‐up . The use of “second‐generation” everolimus‐eluting stent (EES) versus PES has demonstrated lower revascularization rates and better survival rates in high‐risk patients with small coronary artery disease ; furthermore, a recent meta‐analysis showed second‐generation DES (sirolimus eluting stent) to provide superior angiographic and clinical outcome than DCB for the treatment of small coronary vessels . However, there are currently no available data comparing outcomes in patients treated with paclitaxel‐DCB versus EES implantation in this lesion subset.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the BELLO (Balloon Elution and Late Loss Optimization) randomized trial demonstrated that the treatment of small‐vessel disease with a paclitaxel DCB was associated with less angiographic late loss and similar rates of restenosis and revascularization when compared to “first‐generation” paclitaxel‐eluting stents (PES) at 6‐months and a lower incidence of major adverse cardiac event (MACE) at 3‐year follow‐up . The use of “second‐generation” everolimus‐eluting stent (EES) versus PES has demonstrated lower revascularization rates and better survival rates in high‐risk patients with small coronary artery disease ; furthermore, a recent meta‐analysis showed second‐generation DES (sirolimus eluting stent) to provide superior angiographic and clinical outcome than DCB for the treatment of small coronary vessels . However, there are currently no available data comparing outcomes in patients treated with paclitaxel‐DCB versus EES implantation in this lesion subset.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 19 assessing the value of new-generation DES in small vessels. The investigators suggest that the benefit may be greater with novel-generation DES, but data in this regard could not be obtained.In closing, this study provides robust evidence demonstrating the superiority of first-generation SES compared with other classic coronary interventions in patients with small vessels(6). However, from a practical standpoint, the optimal strategy for the current treatment of these lesions cannot be inferred from the present study, as new-generation DES were not included and first-generation SES and PES are no…”
mentioning
confidence: 73%
“…Most ischaemic endpoints are caused by in-stent restenoses, which generally are more frequent in small than in large coronary vessels because the absolute lumen loss after stent implantation comprises a larger proportional percentage of the total lumen diameter. Previous studies in small vessel disease have shown that drug-eluting stents (DES) are superior to bare metal stents (BMS) regarding both angiographic results and clinical events [13], a finding that was corroborated in a recent meta-analysis [4]. While rates for recurrent ischaemic events after implantation of DES are between 5% and 25% with somewhat better results for “limus”- than paclitaxel-eluting stents in a general population [58], there was equipoise between “limus”- and paclitaxel-eluting stents in the subgroup of patients with diabetes mellitus, who normally suffer from small vessel disease [911].…”
Section: Introductionmentioning
confidence: 89%